Innovative Audiovisual Media Integration For Fikih Comprehension In Islamic Junior Schools: Integrasi Media Audio Visual Inovatif Untuk Pemahaman Fikih Di Madrasah Tsanawiyah - Syaiful bahri; Wahyudin Nur Nasution (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The difficulty students face in grasping Islamic jurisprudence, particularly purity rituals, remains a persistent challenge within Indonesian religious junior high schools. Specific Background Many educators persistently rely on conventional lecturing without utilizing diverse instructional tools, which causes learners to remain passive and struggle to connect theoretical religious principles with practical applications. Knowledge Gap Despite recognizing this pedagogical deficit, literature detailing how an educator's inventive synthesis of multimedia tools directly bridges the divide between abstract religious theory and procedural practice in regional madrasahs remains scarce. Aims This research analyzes a teacher's inventive utilization of instructional resources and its contribution to advancing student grasp of purity procedures at MTs Ash-Shofa Medan. Results Utilizing a descriptive qualitative method involving observation and semi-formal interviews, data analysis reveals that the educator innovatively combines visual illustrations, educational videos, and print resources. The strategic deployment of digital materials, coupled with immediate physical practice, successfully concretizes abstract procedural content, significantly elevating student focus, enthusiasm, and motivation during lessons. Novelty This study distinctively highlights the tactical fusion of digital multimedia, print materials, and physical demonstrations to overcome facility limitations in regional educational settings. Implications These pedagogical findings suggest that academic institutions should foster multimedia training and experimental research to further validate digital instructional strategies, ensuring meaningful and interactive religious education. Highlights Strategic deployment of digital tools concretizes abstract purity rituals for religious learners. Combining multimedia presentations with hands-on practice actively bridges the theoretical and practical learning divide. Pedagogical adaptations successfully maintain learner enthusiasm despite physical facility limitations. Keywords Teacher Creativity; Learning Resources; Audiovisual Tools; Student Understanding; Islamic Jurisprudence